Effects of temperature and viscosity on miracidial and cercarial movement of Schistosoma mansoni: ramifications for disease transmission. Issue 2 (February 2020) - Nguyen, K.H.; Gemmell, B.J.; Rohr, J.R.
Graphical abstract: Highlights: High-speed videography quantifies the swimming speed of Schistosoma mansoni larvae. Swimming speeds of larvae increased with temperature and decreased with viscosity. Temperature played a greater role than viscosity in some physiological responses. Schistosoma mansoni larvae travel farther at higher temperatures despite dying sooner. Improved swimming performance in warming climates could increase transmission. Abstract: Parasites with complex life cycles can be susceptible to temperature shifts associated with seasonal changes, especially as free-living larvae that depend on a fixed energy reserve to survive outside the host. The life cycle of Schistosoma, a trematode genus containing some species that cause human schistosomiasis, has free-living, aquatic miracidial and cercarial larval stages that swim using cilia or a forked tail, respectively. The small size of these swimmers (150–350 µm) dictates that their propulsion is dominated by viscous forces. Given that viscosity inhibits the swimming ability of small organisms and is inversely correlated with temperature, changes in temperature should affect the ability of free-living larval stages to swim and locate a host. By recording miracidial and cercarial movement of Schistosoma mansoni using a high-speed camera and manipulating temperature and viscosity independently, we assessed the role each factor plays in the swimming mechanics of the parasite. We found a positive effect of temperature and a negative effect of viscosity on miracidial and cercarial speed. Reynolds numbers, which describe the ratio of inertial to viscous forces exerted on an aquatic organism, were <1 across treatments. Q10 values were <2 when comparing viscosity treatments at 20 °C and 30 °C, further supporting the influence of viscosity on miracidial and cercarial speed. Given that both larval stages have limited energy reserves and infection takes considerable energy, successful transmission depends on both speed and lifespan. We coupled our speed data with mortality measurements across temperatures and discovered that the theoretical maximum distance travelled increased with temperature and decreased with viscosity for both larval stages. Thus, our results suggest that S. mansoni transmission is high during warm times of the year, partly due to improved swimming performance of the free-living larval stages, and that increases in temperature variation associated with climate change might further increase transmission.